The economics of exchange rates in the East Asian countries - Baharumshah, Ahmad Zubaidi (2002)
The recent theoretical and empirical research in international macroeconomics has reestablished the hypothesis of purchasing power parity (PPP) as a long run relationship. This paper highlights some of the difficulties that economist’s had over the past two decades in validating the PPP doctrines. The emphasis is on the exchange rates of the emerging markets of the East Asian economies. This paper argues that with careful application of the nonstationarity time series method, this simple exchange rate and its fundamental variables as techniques that properly capture the dynamic data generating processes of the macroeconomic variables (exchanges rates, current account interest rates, inflation, etc.) are developed. In this paper, the statistical results from the monetary model and its variants are examined to show whether these structural models can replicate the salient features of the exchange rate behavior in the emerging market economics. The focus is on what is predictable and why earlier attempts to model exchange rates failed to produce good forecasts. There is now a growing evidence to suggest that linear models are not always the optimal forecast for the exchange rates.